Pierwsi rolnicy na ziemi kociewskiej - refleksja z najnowszych odkryć archeologicznych - Kochanowski, Marian (Folia Praehistorica Posnaniensia, 2018)
The article is aimed at presentation of a newly discovered Linear Band Pottery settlement at Kościelna Jania, Smętowo Graniczne commune. The site was excavated during rescue works on the Al highway. It has been the largest settlement o f this culture in the Starogard Lake District explored to date. In 21 excavated features, mainly settlement pits, numerous pottery sherds and animal bones (post-consumption remains) were found. Pottery technology and decoration make possible to link these materials with the Note phase and date them back to 430CM1000 be.